Practices of capital structure decisions in Malaysia - Ibrahim, Khairunisah; Haron, Razali; Mat Nor, Fauzias; Ibrahim , Izani; Alias, Norazlan (2011)
Literatures in the area of finance indicate that over the years, academics have not been successful to develop a model to explain decision making in important areas such as capital structure. How firms make their corporate financing decisions has been one of the most extensively researched areas in corporate finance. Yet there is little consensus on how firms choose their capital structure and muchremains to understand the link between theory and practice of capital structure.This study examines the capital structure practices of the Malaysian CEOs by employing a survey analysis on the non-financial listed firms in Malaysia.This study is to observe critically how the dynamics of capital structure choice are influenced by the dispositions of those who make the decisions in practice. Responses are also analyzed conditional upon few firm and management characteristics. The study enriches the literature by discovering the extent to which the capital structure theories are able to explain the corporate financing behavior and practices of Malaysian managers.